Clinical Significance of CYFRA21-1, AFP, CA-153, CEA, and CA-199 in the Diagnosis of Lung Cancer Ocular Metastasis in Hypertension Population - Tang, Jing; Ge, Qian-Min; Huang, Rong; Shu, Hui-Ye; Su, Ting; Wu, Jie-Li; Pan, Yi-Cong; Liang, Rong-Bin; Zhang, Li-Juan; Shao, Yi; Yu, Yao (Frontiers in Cardiovascular Medicine, 2021)
Purpose: To detect lung metastases, we conducted a retrospective study to improve patient prognosis. Methods: Hypertension patients with ocular metastases (OM group; n = 58) and without metastases (NM group; n = 1217) were selected from individuals with lung cancer admitted to our hospital from April 2005 to October 2019. The clinical characteristics were compared by Student’s t-test and chi-square test. Independent risk factors were identified by binary logistic regression, and their diagnostic value evaluated by receiver operating characteristic curve analysis. Results: Age and sex did not differ significantly between OM and NM groups; There were significant differences in pathological type and treatment. Adenocarcinoma was the main pathological type in the OM group (67.24%), while squamous cell carcinoma was the largest proportion (46.43%) in the NM group, followed by adenocarcinoma (34.10%). The OM group were treated with chemotherapy (55.17%), while the NM group received both chemotherapy (39.93%) and surgical treatment (37.06%). Significant differences were detected in the concentrations of cancer antigen (CA) -125, CA-199, CA-153, alpha fetoprotein (AFP), carcinoembryonic antigen (CEA), cytokeratin fraction 21-1 (CYFRA21-1), total prostate‐specific antigen, alkaline phosphatase, and hemoglobin (Student’s t-test). Binary logistic regression analysis indicated that CA-199, CA-153, AFP, CEA, and CYRFA21-1 were independent risk factors for lung cancer metastasis. AFP (98.3%) and CEA (89.3%) exhibited the highest sensitivity and specificity, respectively, while CYRFA21-1 had the highest area under the ROC curve value (0.875), with sensitivity and specificity values of 77.6% and 87.0%, respectively. Hence, CYFRA21-1 had the best diagnostic value.